The imaging features of ectopic spleen: which modality is more consistent? A cases series report and literature reviews - Xiao, Mingyue; Liang, Jiayi; Ren, Jie; Zheng, Rongqin; Wu, Lili (Frontiers in Oncology, 2024)
Ectopic spleen (ES) is a rare condition. It is difficult to diagnose with conventional imaging modalities.In this case series, we presented the imaging features of 3 misdiagnosed ES cases in our hospital and previous reported cases to compare the consistency of enhancement patterns among different imaging modalities with varied phases. Finally, 22 cases were reviewed. We determined that variable arterial phase enhancement and persistent enhancement throughout the portal and delayed phases are present in contrast-enhanced ultrasound (CEUS) imaging of the ES, and found the arterial phase of CEUS had the highest consistency compared with computerized tomography (CT) and magnetic resonance imaging (MRI).